Generation and analysis of pseudohypoaldosteronism type II knock‐in mice caused by a nonsense KLHL3 mutation in the Kelch domain. Issue 6 (27th May 2022) - Lin, Chien‐Ming; Sung, Chih‐Chien; Yang, Sung‐Sen; Chen, Ying‐Chuan; Huang, Shih‐Ming; Lin, Shih‐Hua
Abstract: Mutations in the Kelch‐like 3 ( KLHL3 ) gene are the most common cause of inherited pseudohypoaldosteronism type II (PHAII) featuring thiazide‐sensitive hypertension and hyperkalemic metabolic acidosis. Although Klhl3 R528H /+ knock‐in (KI) mice carrying a missense mutation in the Kelch repeat domain have been reported, nonsense KLHL3  mutations in the same domain that cause PHAII have not been fully investigated in vivo. We generated and analyzed Klhl3  KI mice harboring a nonsense W523X mutation (corresponding to the human KLHL3  W470X mutation). Both heterozygous and homozygous Klhl3 W523X /+ KI mice exhibited typical PHAII with low‐renin hypertension, hyperkalemia with reduced renal potassium excretion, and hyperchloremic metabolic acidosis. Their kidney tissues showed the presence of Klhl3  mRNA and increased Klhl3 protein levels along with enhanced downstream Wnk1/4‐Spak/Osr1‐N(k)cc phosphorylation. Increased protein expression of total Spak, phosphor(p‐)Spak, total Ncc, and p‐Ncc from urinary extracellular vesicles (uEVs) also confirmed the activation of the Wnk‐mediated Ncc pathway. In vitro studies showed that the human KLHL3  W470X mutation resulted in increased KLHL3 protein stability and disrupted its binding affinity for WNK1/4, leading to the attenuated degradation and increased abundance of total WNKs. In conclusion, nonsense Klhl3 W523X /+ mice recapitulating PHAII phenotypes exhibit Klhl3 protein stability, abrogating its binding to Wnks, with enhanced Ncc expression in the kidney tissue and even in uEVs. Activation of the WNK‐mediated Na + ‐Cl − co‐transporter reiterated the in vivo pathogenic role of nonsense KLHL3  mutations in PHAII.